REKONSILIASI ISLAM DAN SAINS DALAM PERSPEKTIF NIDHAL GUESSOUM - Zulpa Makiah (Khazanah: Jurnal Studi Islam dan Humaniora, 2021)
This paper describes Nidhal Guessoum, who tried to reconcile the epistemic between the Islamic tradition and modern science. The method used is descriptive content analysis. Nidhal sees that efforts to build relations between religion and science are still simplistic. He seeks to uncover the deadlock between the science of religion and philosophy and to present the principles of reconciliation of Islam and science more completely and systematically. This reconciliation effort departs from his critique of the condition of education and Arab society as well as the Islamic world as a whole, as well as the developing thoughts on the relationship between religion and science, which are sometimes too simplistic, both Sardar's ijmāli model, i'jāz an-Najjar model, and Islamization of al-Faruqi's model of knowledge. In Nidhal's view, these methods contain weaknesses, so those other alternatives are needed. The steps taken by Nidhal are to build a foundation for the creation of a harmonious relationship between science, religion and philosophy. He proposed a quantum approach through (1) the principle of no conflict between religion and science, (2) layered interpretation of the Qur'an, (3) theistic falsification.Tulisan ini berupaya menjelaskan pemikiran Nidhal Guessoum yang berusaha melakukan rekonsiliasi epistemik antara tradisi Islam dan sains modern. Metode yang digunakan dalam membaca karya Nidhal adalah dengan menggunakan analisis isi (content analysis) secara deskriptif. Nidhal melihat upaya dalam membangun relasi antara agama dan sains masih bersifat simplistik. Nidhal berusaha menyingkap kebuntuan titik temu antara sains agama dan filsafat serta menghadirkan prinsip-prinsip rekonsiliasi Islam dan sains secara lebih lengkap dan sistematis. Upaya rekonsiliasi ini berangkat dari kritiknya terhadap kondisi pendidikan dan masyarakat Arab serta dunia Islam secara keseluruhan, juga terhadap pemikiran-pemikiran yang berkembang mengenai hubungan antara agama dan sains yang terkadang terlalu simplistik, baik model ijmāli Sardar, model i’jāz an-Najjar, maupun Islamisasi pengetahuan model al-Faruqi. Metode-metode itu dalam pandangan Nidhal mengandung kelemahan-kelemahan sehingga diperlukan alternatif lain. Langkah yang dilakukan Nidhal adalah membangun landasan terciptanya hubungan yang harmonis diantara sains, agama dan filsafat. Nidhal mengusulkan pendekatan kuantum melalui: (1) prinsip tidak ada pertentangan antara agama dan sains; (2) penafsiran berlapis terhadap al-Qur’an; (3) falsifikatif teistik.